2016
DOI: 10.1136/neurintsurg-2016-012515
|View full text |Cite
|
Sign up to set email alerts
|

A population-based incidence of acute large vessel occlusions and thrombectomy eligible patients indicates significant potential for growth of endovascular stroke therapy in the USA

Abstract: BackgroundData on large vessel strokes are important for resource allocation and infrastructure development.ObjectiveTo determine an annual incidence of large vessel occlusions (LVOs) and a thrombectomy eligible patient population.MethodsAll patients with acute ischemic stroke discharged over 3 years from a tertiary-level hospital serving a large geographic area were evaluated for an LVO (M1, internal carotid artery terminus, basilar artery). The incidence of LVO was determined for the hospital's 4-county prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
122
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(133 citation statements)
references
References 26 publications
4
122
0
2
Order By: Relevance
“…Given the recently extended time window for endovascular therapy in acute stroke, the number of patients receiving treatment would perhaps increase as 2 patients in the late AIS group presented within an extended window but did not receive endovascular treatment [18]. The frequency of LVO in our study is comparable to the reported frequency of acute LVO from 11 to 46% in non-LVAD population [19][20][21]. The observation that nearly 1 in 3 persons had acute LVOs suggests that CTA study should be pursued and the endovascular therapy is feasible especially when the presence of acute LVO is known to carry a high mortality rate and poor functional outcome [21,22].…”
Section: Discussionsupporting
confidence: 76%
“…Given the recently extended time window for endovascular therapy in acute stroke, the number of patients receiving treatment would perhaps increase as 2 patients in the late AIS group presented within an extended window but did not receive endovascular treatment [18]. The frequency of LVO in our study is comparable to the reported frequency of acute LVO from 11 to 46% in non-LVAD population [19][20][21]. The observation that nearly 1 in 3 persons had acute LVOs suggests that CTA study should be pursued and the endovascular therapy is feasible especially when the presence of acute LVO is known to carry a high mortality rate and poor functional outcome [21,22].…”
Section: Discussionsupporting
confidence: 76%
“…Given an annual estimated incidence of 691 650 AISs per year in the USA,34 rates of LVO exceeding 20% would represent substantially greater numbers of potentially thrombectomy-eligible patients than what is reflected by current procedural volumes. In a study of patients with AIS, Rai et al used institutional data to compute an LVO rate of 11%, and population analyses to estimate a national incidence of 77 569 new LVOs each year 17. The authors subsequently emphasized that the disparity between current procedural volumes and these estimates reflected a potential 2–5-fold increase in annual thrombectomy volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The real value of LVO prevalence is not yet precisely known; it ranges from 4.7% to 24% (Dozois et al., 2017; Rai et al., 2017). As PPV strongly depends on LVO prevalence, we provided expected PPV for populations with 10% and 20% LVO prevalence (Table 5).…”
Section: Discussionmentioning
confidence: 99%